Isolation and purification of antioxidant peptides from swim bladder of grass carp (Ctenopharyngodon idella) - Suxin Li; Jinhui Gu; Biluan Zhong; Rui Feng; Hao Pan; Yiyi Liu; Wenzheng Shi (Aquaculture and Fisheries)
Swim bladder is a kind of material with rich nutritional value, wide access and a good source of collagen. In order to make it more fully utilized and absorbed by human body, using grass carp swim bladder as raw material and alkaline protease-neutral protease to prepare collagen peptide, the degree of hydrolysis can reach 36.91%. The results proved that after purification by ultrafiltration membrane and gel column chromatography, the antioxidant activity of GCP generally increased with the increase of concentration, and the smaller the molecular weight of GCP obtained after separation and purification, the stronger the overall antioxidant activity. Among them, the ABTS+ scavenging rate of GCP with a certain molecular weight was 88.64%. Moreover, GCP also has good SOD scavenging ability and ferrous ion chelating ability. The total antioxidant activity of GCP-II purified by G15 gel column is great, for it exerts considerable antioxidant capacity at a lower concentration.